2019
DOI: 10.3390/jcm8020166
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Measurement of Peri-Implant Crestal Bone Loss (CBL)

Abstract: The etiology of peri-implant crestal bone loss is today better understood and certain factors proposed in the past have turned out to not be of concern. Regardless, the incidence of crestal bone loss remains higher than necessary and this paper reviews current theory on the etiology with a special emphasis on traditional and innovative methods to assess the level of crestal bone around dental implants that will enable greater sensitivity and specificity and significantly reduce variability in bone loss measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 123 publications
(162 reference statements)
0
50
0
1
Order By: Relevance
“…Dental implants are ordinarily used in clinics for the replacement of teeth. Even though many advances have occurred in materials, techniques, also in the design of the implant, implant failure in treatment is a primary concern for dentists and patients [ 1 , 2 ]. “A graft that sets tightly or deeply into the alveolar bone.” is defined as an implant.…”
Section: Introductionmentioning
confidence: 99%
“…Dental implants are ordinarily used in clinics for the replacement of teeth. Even though many advances have occurred in materials, techniques, also in the design of the implant, implant failure in treatment is a primary concern for dentists and patients [ 1 , 2 ]. “A graft that sets tightly or deeply into the alveolar bone.” is defined as an implant.…”
Section: Introductionmentioning
confidence: 99%
“…After implant surgery, bone remodeling resulting from a biological process is expected, and studies have shown that the amount of vertical bone is variable considering biological and mechanical aspects [6,7,8]. However, in the case of serious complications, bone resorption may be advanced and result in loss of osseointegration and subsequent implant failure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Stress breakers/relievers in the implant would greatly benefit the surrounding bone by decreasing the micro fractures due to overloading and the consecutive bacterial infiltration, decreasing bone loss, especially in the oral cavity. Other advantages in the case of dental implants might include: More prosthetic solutions, increased patient comfort, and an overall longer implant lifespan [14,16].…”
Section: Introductionmentioning
confidence: 99%